PENGARUH IKLAN DAN KUALITAS PRODUK TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PRODUK SIMPATI (Studi Pada Pengguna Kartu Simpati di Wilayah Kota Malang Jawa Timur) - Bilal, Muhamad; Rohman, Fatchur (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect of Advertising and Product Quality Consumer Purchase Decision Against Simpati Product  (Studies in Simpati Card Users in Malang district of East Java). Types of research used in this research is explanatory research  (research  explanation)  that aims  to  explain the  causal relationship between  the causal variables  through hypothesis  testing. Data were collected  through  a questionnaire survey  to  Simpati  card  users  in the city of Malang.  The sampling technique  used was  purposive  sampling  and  obtained a sample of  60  respondents.  To test  the  hypothesis proposed  in this study  used regression analysis. Regression analysis showed that advertising and product quality as well as partial  simultaneously  have  a significant influence  on purchasing decisions. Between the  two variables,  variables  which  have a  dominant  influence  on purchasing decisions  is advertising variable. Based on this analysis, suggestions are given  in  the advertisement Simpati seatraktif delivery must be made possible to be able to attract the attention of consumers, delivery  time and  location of ad placements  should be  tailored to the target  of  the ad,  and  use  resources more messages are generally not accepted by  the or some circles only. Meanwhile,  in terms of the quality of the following suggestions should be used as a consideration which,  always  present  things that are  new  and  innovative  for consumers,  and provide  packages  attractive  prices  and  promotions  are  tailored to the  needs of consumers. Keywords: advertising, product quality, and purchase decision